Respon Siswa Terhadap Pembelajaran Tarkib Berbasis Mind Mapping di Masa Pandemi Covid-19 - Darsa Muhammad; Muassomah Muassomah (Institut Agama Islam Negeri (IAIN) Metro, 2021)
This research aims to show the practice of tarkib learning using mind mapping learning strategies and determine the students' responses to applying the learning model at MA Almaarif Singosari Malang. This learning process has a limited duration of learning meetings during the Covid-19 pandemic. This research is qualitative and descriptive. The data source consisted of students of class XII MIA 3 second session of MA Almaarif Singosari Malang. Data collection techniques were carried out by interview, questionnaire, and documentation. The data validation is used the triangulation technique. The data analysis technique is used the Mile and Huberman, namely: data collection and checking, data reduction, data presentation, and inference. This study's results indicate that students' positive responses to the application of the mind mapping learning model in tarkib learning were much higher than the negative responses. Therefore, seen from the perspective of student responses, the mind mapping learning model is suitable for tarkib learning in class, especially for courses with limited face-to-face time duration.